KelpLink: An AI-Driven Mobile Platform for Sustainable Seaweed Farming - Divya Surve; Rohit Patil; Atharva Birwadkar; Shardul Palande; Vedant Mantri (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2026)
KelpLink is an AI-powered platform designed to digitally transform India’s seaweed farming ecosystem. By integrating artificial intelligence, cloud computing, and multilingual support, the system enhances agricultural productivity, transparency, and environmental sustainability. It empowers coastal farmers to accurately identify seaweed species, monitor health, and directly connect with certified buyers via a secure digital marketplace. Key features include encrypted messaging, AI-driven sustainability dashboards for estimating carbon sequestration, and robust data protection using modern web architectures like Next.js, Node.js, and MongoDB Atlas. Initial testing demonstrates improvements in operational transparency and market participation. Ultimately, KelpLink aims to integrate IoT and blockchain technologies, positioning itself as a pioneering solution for India’s Blue Economy and Digital Ocean initiatives